Design Factors Affecting the Fixation of Cervical Disc Replacements: A Biomechanical Analysis - Wahbeh, Jenna M; Ballester, David A; Ebramzadeh, Edward; Sangiorgio, Sophia N (Spine (Philadelphia, Pa. 1976), 2025)
Biomechanical study. The goal of the present study is to explore the connection between various cervical disc replacement designs and the overarching risk of migration. Migration of cervical disc replacements has become an increasingly prevalent complication in clinical use. Despite this, there is a lack of biomechanical studies addressing the relationship between implant design and migration. Five cervical disc replacement designs were tested in rigid polyurethane models. Before testing, each device had measurements taken of important features: endplate surface roughness, extruding keel/fin heights, device height, ball contact arc, and coverage angle. Each device was subjected to 10,000 cycles of all spinal rotations, and a combined loading pattern of all 3 rotations was applied simultaneously. Sagittal and coronal plane micromotions at the bone-implant interface were continuously measured through all testing. Micromotions were then compared as a function of device design, loading type, and specific fixation features. Overall, one ball-and-socket device, the PCM, had larger cyclic micromotions than all other devices during flexion/extension and lateral bending ( P <0.06). A different ball-and-socket device, the Prestige-ST, had larger overall migrations in the sagittal plane during axial rotation ( P <0.01). When comparing specific device features, trends were identified for three variables: keel/fin height, ball contact arc, and coverage angle. A smaller keel/fin and coverage angle and a larger ball contact arc were associated with an increase in micromotion ( P <0.05, <0.01, <0.01, respectively). This study presents the first quantification of micromotion, representing initial fixation, in cervical disc arthroplasty. Further, findings were generally consistent with clinical literature regarding device migration. This study has identified device-specific trends that may influence micromotion in vivo. These findings or methodology can be utilized to identify successful devices for patients or offer valuable insights into future cervical disc designs.